Comparison of nebulized Salbutamol versus Adrenaline in the treatment of wheeze associated respiratory tract infection - S., Sireesha; Prasad, B. S.; J., Suresh (International Journal of Contemporary Pediatrics, 2017)
Background: Wheezing related to respiratory infections is common in infancy and early child hood. In 1-3% of all infants these infections are severe enough to require hospitalization. Most episodes of wheezing in early life are of viral origin and form a heterogeneous group with different outcomes. The objectives of this study were to assess the efficacy of bronchodilators in wheeze associated respiratory infection and to comparing the efficacy of a nebulized nonspecific adrenergic agonist -1 adrenaline with a nebulized beta-2 specific agonist salbutamol for the treatment of the wheeze associated respiratory tract infection. Methods: The study was conducted in children reporting to the Pediatric Department Government General Hospital in Kakinada. The study period was 6 months from January to June 2014. Children between the ages of two months to two years attending the hospital with the clinical diagnosis of bronchiolitis were enrolled. Results: 30 children were enrolled. 22 (73.3) were in age group of 2 months to 1 year and 8 (26.7%) were in age group of 1-2 years. There is no added advantage of decreasing the respiratory rates, wheezing and retractions of one over the other groups. Conclusions: It can be inferred that bronchodilators, both nebulized adrenalin and salbutamol are useful in relieving symptoms and improving oxygenation in wheezy infants with clinical diagnosis of WRTI. No drug is said to be better over the other.